Finest frugt - om ‘den Vartou Kjællingepræst’: En guide til Grundtvig-Studier 1948-2008, I - Jørgensen, Aage (Grundtvig-studier, 2009)
Finest frugt - om ‘den Vartou Kjællingepræst En guide til Grundtvig- Studier 1948-2008,I[Fruit of the finest - concerning ‘the Vartov Old Biddies ’pas torA guide to Grundtvig-Studier 1948-2008, I]By Aage Jørgensen As early as 1948, the Grundtvig Society of 8 September 1947 launched an annual journal, Grundtvig-Studier (Grundtvig Studies). Since then, the journal has published a significant part of the subsequent research on Grundtvig, including important debate on the many Grundtvig dissertations that have appeared since World War II. This anniversary article reviews the content of the sixty volumes that have hitherto been issued. Despite its cross-disciplinary character, the material is here presented in a traditionally systematised format.The opening section deals with studies in bibliography, diplomatics and biography, and is followed by a series of fairly lengthy sections characterising: (1) material pertaining to the history of ideas and concerned with Grundtvig’s views on life and history together with his relation to Romantic philosophy, Northern mythology and the contemporary way of thinking as a whole; (2) material relating to literary history and aesthetics, with emphasis upon a series of exemplary contributions by particular authors (Gustav Albeck, Helge Toldberg, Jørgen Elbek, Flemming Lundgreen-Nielsen, Sune Auken and, as regards the influence of Anglo-Saxon upon Grundtvig, S. A. J. Bradley); and (3) the theological material, with focus especially upon the impact of Kaj Thaning’s designation of 1832 as a decisive turning-point in Grundtvig’s life, and upon Grundtvig’s relationship to Luther, Kierkegaard and mystic tradition. The exploration of Grundtvig's hymns and sermons is treated in separate sections; and finally there is a section concerned with illustration of his political endeavours. For reasons of space, contributions to the journal on Grundtvig’s educational deliberations and their significance for Danish schools, especially the folk high schools, together with the overall subsequent reception of his thinking (within Denmark and out in the wider world) will be reserved for discussion in Grundtvig-Studier 2010.